Relationship on Leadership Support with Nurser Compliance Identifying Patients in the Implementation of Patient Safety in Datu Beru Central Aceh Regional General Hospital - Mualimin Mualimin; Thomson P Nadapdap; Deli Deli (Journal La Medihealtico, 2020)
The patient safety mission at the hospital is to prevent patient safety incidents from occurring, the number of incidents is said to be like an iceberg phenomenon. The incidence rate in Indonesia based on data from the Joint Commission International (2012) shows that as many as 13% due to surgical errors and 68% due to blood transfusion errors. This study aims to analyze the relationship between leadership support and compliance with nurses in identifying patients in the implementation of patient safety in the Datu Beru Aceh Hospital. Tengah. The research design used a quantitative analytic survey with a cross-sectional design. The population of all nurses working in the Women's Internal Medicine Room at Datu Beru Hospital, Central Aceh was 34 people. The sampling technique used total sampling. Data analysis was carried out by univariate, bivariate and multivariate with chi_square. The results of the research variable Leadership Support with Nurse Adherence obtained p-value = 0,000, meaning that there is a relationship between leadership support and nurse compliance to identify patients in the application of patient safety. Multivariate analysis of leadership support variables obtained sig value of 0.000 <p = 0.05, which means that there is a significant influence of the leadership support variable on nurse compliance. There is a relationship between leadership support and the compliance of nurses to identify patients in the application of patient safety and there is a significant effect.